HUBUNGAN TINGKAT KEPERCAYAAN DIRI DAN MOTIVASI DENGAN KETERAMPILAN GERAK DASAR SEPAKBOLA - Yudha Purnama Putra; Frans Nurseto; Surisman Surisman (JUPE (Jurnal Penjaskesrek), 2013)
This study aims to determine the relationship of the level of confidence and motivation with basic motor skills of football in junior high school students' extracurricular 8 Bandar Lampung. The research method used was descriptive correlational. The sample used is a student extracurricular N 8 junior football in Bandar Lampung, amounting to 30 students. The analysis showed that the level of confidence had a significant association with the basic motor skills of football at 0.687. Correlation coefficient with the motivation of the basic motor skills of football at 0.419. While the correlation coefficient confidence and motivation with the basic skills of soccer motion for 0.774. It means confidence and motivation to have a relationship 'stronger' with basic movement skills of football at junior high school students' extracurricular 8 Bandar Lampung.Kata kunci : deskriptif korelasional, percaya diri, motivasi, sepakbola